The Effectiveness of Sexual Education Video-Based Learning in Improving Adolescents’ Knowledge on Preventing Premarital Pregnancy to Support Sustainable Development Goals (SDGs) - Fitri A Sabil; Wa Mina La Isa; Amriati Mutmainnah; Rusni Mato; Darwis; Muzakkir (Jurnal Penelitian Pendidikan IPA, 2026)
Premarital pregnancy among adolescents remains a major reproductive health problem that may negatively affect adolescents’ physical, psychological, and social well-being. This study aimed to determine the effectiveness of sexual education video-based learning in improving adolescents’ knowledge regarding premarital pregnancy prevention at SMAN 21 Makassar. This study used a quantitative quasi-experimental design with a one-group pretest-posttest approach. The population consisted of 61 tenth-grade students selected using a total sampling technique. The intervention consisted of a 15-minute sexual education video discussing reproductive health, risk factors, and prevention of premarital pregnancy. Data were collected using a validated questionnaire and analyzed using the Wilcoxon Signed Rank Test. Before the intervention, most respondents had poor knowledge (85.24%), while after the intervention, the majority demonstrated good knowledge (93.44%). Statistical analysis showed a significant increase in adolescents’ knowledge after the intervention (p < 0.01). Sexual education video-based learning can be used as an effective educational strategy to improve adolescents’ reproductive health knowledge and support Sustainable Development Goals (SDGs).